APPLICATIONS OF ROUTINE CARDIAC MRI PULSE SEQUENCES – A CONTEMPORARY REVIEW - Georgi Valchev; Ralitsa Popova; Samar El Shemeri; Yana Bocheva; Nataliya Usheva; Sonya Galcheva; Violeta Iotova; Yoto Yotov (Journal of IMAB, 2019)
Cardiac magnetic resonance imaging is a relatively novel method, which has recently vastly expanded its applications and usefulness. It is a non-ionizing method, with very few contraindications, allowing for characterization of the full spectrum of cardiac diseases. This is done by means of performing a multitude of specially-tailored pulse sequences, each of which images different aspects of morphology and pathology. When putting together all the data, acquired from the separate sequences, a skilled radiologist can provide a comprehensive and insightful interpretation to great clinical benefit. There are morphological, functional, quantitative, and contrast-based imaging sequences, but not all of them are performed on every patient – due to time constraints every imaging protocol is individually calibrated to suit the corresponding clinical query.